2023
DOI: 10.2169/internalmedicine.0552-22
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features and the Prevalence of Oxyntic Gland Neoplasm: A Single-center Retrospective Study

Abstract: Objective We explored the clinicopathological characteristics and disease frequency of oxyntic gland neoplasms (OGNs). Methods We retrospectively evaluated the data of patients pathologically diagnosed with OGN at an internal medicine clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…This estimation is based on the findings of a large retrospective study of 13,240 upper gastrointestinal endoscopies performed on 7,488 patients at an outpatient internal medicine and endoscopy clinic in Japan (Asahara Clinic, Akashi, Japan). Of note, the authors of the study note that their estimated period prevalence is much larger than previously reported [ 4 ]. Furthermore, cases of OGA reported outside of Japan are exceptionally scarce [ 5 ].…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…This estimation is based on the findings of a large retrospective study of 13,240 upper gastrointestinal endoscopies performed on 7,488 patients at an outpatient internal medicine and endoscopy clinic in Japan (Asahara Clinic, Akashi, Japan). Of note, the authors of the study note that their estimated period prevalence is much larger than previously reported [ 4 ]. Furthermore, cases of OGA reported outside of Japan are exceptionally scarce [ 5 ].…”
Section: Introductionmentioning
confidence: 59%
“…H. pylori does not seem to contribute to the development of gastric-type adenocarcinomas, which include foveolar, pyloric, and fundic-gland type related adenocarcinomas [ 4 , 17 ]. In contrast to H. pylori infection-associated gastric carcinomas, most OGA/GA-FG involve the upper third of the stomach (80%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations